Clinical use of thrombin generation assays. (8th October 2021) - Binder, Nikolaus B.; Depasse, François; Mueller, Julia; Wissel, Thomas; Schwers, Stephan; Germer, Matthias; Hermes, Björn; Turecek, Peter L.
Abstract: Determining patient's coagulation profile, i . e . detecting a bleeding tendency or the opposite, a thrombotic risk, is crucial for clinicians in many situations. Routine coagulation assays and even more specialized tests may not allow a relevant characterization of the hemostatic balance. In contrast, thrombin generation assay (TGA) is a global assay allowing the dynamic continuous and simultaneous recording of the combined effects of both thrombin generation and thrombin inactivation. TGA thus reflects the result of procoagulant and anticoagulant activities in blood and plasma. Because of this unique feature, TGA has been widely used in a wide array of settings from both research, clinical and pharmaceutical perspectives. This includes diagnosis, prognosis, prophylaxis, and treatment of inherited and acquired bleeding and thrombotic disorders. In addition, TGA has been shown to provide relevant information for the diagnosis of coagulopathies induced by infectious diseases, comprising also disturbance of the coagulation system in COVID‐19, or for the assessment of early recurrence in breast cancer. This review article aims to document most clinical applications of TGA.